From transactional to transcendent inclusion: A document analysis of how universities in South Africa conceptualize the inclusion that responds to the transformation quest - Ewuoso, C.; Obasa, E. (South African Journal of Higher Education, 2026)
Background Transformation is a key priority for universities in South Africa. While an important way universities in South Africa have tried to be transformative is through greater emphasis on inclusion, no document analysis or synthesis exists that articulates the account of inclusion that responds to the quest for transformation by South African universities. We address this gap. Methods Precisely, this document analysis articulates the account of inclusion that responds to the quest for transformation emanating from publicly available 48 transformation instruments of key South African universities. Results This analysis found that transactional, transformational, and transcendent inclusion are three forms of inclusion that respond to the quest for transformation. There are two prominent areas targeted for inclusion work: place and institutional culture. Additionally, underlying these inclusion forms are principles of pragmaticism, deep inclusion work and relevance. Conclusion Understanding how universities conceptualize inclusion is the critical first step towards exploring what more needs to be done to ensure inclusion work in South Africa adequately responds to the transformation quest.